Advances in Real-time Information Networks - Sandrasegaran, Kumbesan (UTS ePRESS, 2013)
Our scholarly peer reviewed workshop papers publish the latest, high quality research work from UTS researchers. They cover all aspects of communication, computing and ICT. Our editorial boards and reviewers are from researchers and experts in these fields.